2021
DOI: 10.1038/s41598-021-02874-z
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of novel combinations of SARS-CoV-2 spike receptor binding domain variants in Senegal

Abstract: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) lineages that carry mutations in the spike gene are of concern for potential impact to treatment and prevention efforts. To monitor for new SARS-CoV-2 mutations, a panel of specimens were sequenced from both wave one (N = 96), and wave two (N = 117) of the pandemic in Senegal by whole genome next generation sequencing. Amongst these genomes, new combinations of SARS-CoV-2 spike mutations were identified, with E484K + N501T, L452R + N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In several west African countries, the VOC Alpha and the VOI Eta constituted the two main competing variants. 31 34 These data were confirmed by the analysis of west African sequences deposited in GISAID. From November 2020 to May 2021, 1,901 complete and high-coverage genomes were deposited by the 16 west African countries ( Supplemental Table 5 ).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…In several west African countries, the VOC Alpha and the VOI Eta constituted the two main competing variants. 31 34 These data were confirmed by the analysis of west African sequences deposited in GISAID. From November 2020 to May 2021, 1,901 complete and high-coverage genomes were deposited by the 16 west African countries ( Supplemental Table 5 ).…”
Section: Resultssupporting
confidence: 53%
“…In Senegal, lineage B.1.416 represented 59.4% of sequenced strains. 31 No lineage corresponding to a SARS-CoV-2 VOC circulated during this first epidemic wave in west Africa.…”
Section: Resultsmentioning
confidence: 99%
“…reported the emergence of L452M in clade 20A during the second wave of COVID-19 on December 2020 to March 2021 in Senegal. 17 In Pt 5, we detected S-E484Q on Day 3 after RDV treatment and N501Y before treatment, whereas it was reverted to N501I after treatment. Our findings showed that S-E484Q could appear during treatment with RDV in the absence of mAbs therapies.…”
Section: Sars-cov-2 Genome Analysismentioning
confidence: 82%
“…It seems that S‐L452M in Pt 4 might be a transient variation that was triggered after using three courses of RDV in long‐term infection independently. In addition, Ahouidi et al reported the emergence of L452M in clade 20A during the second wave of COVID‐19 on December 2020 to March 2021 in Senegal 17 …”
Section: Discussionmentioning
confidence: 99%
“…Though respiratory, enteric, and opportunistic pathogens are not optimally detected in plasma, SARS-CoV-2 was found once in Bounkiling from a patient (BK247) received in April 2021; despite only recovering 8% of the genome, enough coverage in the spike protein was present to putatively assign it to the Alpha variant (lineage B.1.1.7), which was indeed present in the country at the time ( Ahouidi et al, 2021 ; Perez et al, 2022 ). We also identified human rotavirus A (HRV-A) infections in two adults from Bounkiling (BK080 and BK183); of these two, the patient corresponding to specimen BK183 presented to the clinic with fever and vomiting, consistent with rotavirus infection.…”
Section: Resultsmentioning
confidence: 99%